Between Divinity and Liberty: Rethinking Religious Freedom under Indonesia’s Constitution - Muhammad Ramadhan Giri Wardana; Abdul Ghoffar Husnan; Muhtar Said; Kartini Laras Makmur (Pancasila: Jurnal Keindonesiaan, 2025)
This study examines the implementation of religious freedom in Indonesia through the lens of constitutionalism, focusing on the interpretive ambiguity between the foundational state principle of Ketuhanan Yang Maha Esa (Belief in the One and Only God) and the constitutional guarantee of religious freedom set out in Article 29(2) of the 1945 Constitution. This tension becomes particularly apparent when Article 28E, which affirms individual religious freedom, is curtailed by Article 28J, which allows the state to impose limitations on the public interest. Using a juridical-normative approach, this research investigates how Ketuhanan Yang Maha Esa is embedded within Indonesia’s legal framework and how varying constitutional interpretations influence the realisation of religious freedom. The findings reveal that, although the 1945 Constitution formally guarantees religious freedom, its implementation is often obstructed by administrative requirements, such as the mandatory declaration of religion in official identification documents, that fall short of international human rights standards. The study argues that this inconsistency stems from restrictive legal interpretations and the lack of coherent implementation. It calls for a more inclusive and balanced interpretative framework that upholds both constitutional principles and international human rights norms. The study’s key academic contribution lies in elucidating the complex relationship between Ketuhanan Yang Maha Esa and religious freedom, offering critical insights into the broader application of human rights within Indonesia’s constitutional order.